Taking Your iPhoto '11 to the Max - Grothaus, Michael (Apress : Imprint: Apress, 2011)
Taking Your iPhoto '11 to the Max walks users through Apple's most popular software application in the iLife suite-iPhoto. This book helps readers use iPhoto to its fullest to organize and create digital memories and keepsakes. Learn all about Apple's newest version of iPhoto-iPhoto '11 Explore iPhoto, one menu button at a time Walk-through tutorials guide you step-by-step.